2021
DOI: 10.3389/fimmu.2021.663106
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytogenics and Galactomannan Oligosaccharides in Low Fish Meal and Fish Oil-Based Diets for European Sea Bass (Dicentrarchus labrax) Juveniles: Effects on Gill Structure and Health and Implications on Oxidative Stress Status

Abstract: An effective replacement for fish meal (FM) and fish oil (FO) based on plant-based raw materials in the feed of marine fish species is necessary for the sustainability of the aquaculture sector. However, the use of plant-based raw materials to replace FM and FO has been associated with several negative health effects, some of which are related to oxidative stress processes that can induce functional and morphological alterations in mucosal tissues. This study aimed to evaluate the effects of dietary oligosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Similar findings were made in a previous study on Psetta maxima , which showed that a moderate amount of dietary cysteine (0.3%) enhanced the SGR levels and the mean final weight of P. maxima and improved its growth performance ( 20 ). Oxidative stress and immune capacity reduction caused by low fishmeal content are the main reasons for reduced growth performance ( 8 , 9 , 46 ). In the present study, there were many reasons that cysteine supplementation improved the growth performance of golden pompano in low fishmeal conditions, such as the increased abundance and diversity of gut microbes ( 31 ), increased antioxidant capacity ( 47 , 48 ), and improved immune ability ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were made in a previous study on Psetta maxima , which showed that a moderate amount of dietary cysteine (0.3%) enhanced the SGR levels and the mean final weight of P. maxima and improved its growth performance ( 20 ). Oxidative stress and immune capacity reduction caused by low fishmeal content are the main reasons for reduced growth performance ( 8 , 9 , 46 ). In the present study, there were many reasons that cysteine supplementation improved the growth performance of golden pompano in low fishmeal conditions, such as the increased abundance and diversity of gut microbes ( 31 ), increased antioxidant capacity ( 47 , 48 ), and improved immune ability ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of response in the endogenous antioxidant defenses could be present and associated with the antioxidant properties of the phytogenic compounds, making them capable of inhibiting ROS formation and quenching them once they are formed [ 54 , 55 , 56 ]. Indeed, our previous studies in this mucosal tissue indicated that both functional additives can reduce gill oxidative-stress status in basal conditions after dietary supplementation [ 42 ]. Between the different plant-origin biomolecules, the flavonoids are polyphenolic compounds with high antioxidant properties and can be found in a wide spectrum of plant extracts as garlic oil and labiate plant extracts, such as origanum [ 57 ] and thyme [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to fish-gill structural integrity like that originated by oxidative-stress processes may lead to degenerative processes such as gas-exchange disturbances [ 61 ] and impairments to immune functions [ 62 ]. In our previous studies, Torrecillas et al (2021) observed the ability of GMOS and PHYTO diets to induce higher gill gene expression of zo-1 and ocln , respectively, in basal conditions [ 42 ]. In the present study, the use of different dietary treatments did not affect fish gill ocln and zo-1 relative gene expression in the early hours after both stress challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations